(untitled) (Sociologisk Forskning, 2009)
The re-unification of a family of nations: usages of the family metaphor in the EU This article analyses usages of the family metaphor in the EU. It starts up with a scrutiny of feminist theories of the nation-as-family metaphor. Introducing the concept of domopolitics, the author infers that the family, on the one hand, connotes to feelings of security and homelyness and, on the other hand, fears of the well-known, of immanent threats to in-group cohesion. The significance of the family metaphor in the EU rhetoric connects to a renewed emphasis on distinct values, principles and norms that balance the otherwise technocratic image of the EU. He further applies the nation-as-family metaphor to contemporary EU rhetoric. In the analysis, he infers that all three dimensions of the metaphor (ethnic, civil and hierarchic) are manifest in the EU political language making its use an enterprise that strives at moving beyond, but not completely away from the nation-state paradigm.